Fetal hepatic hemangioma: a case report - Shresth, Manindra; Bajracharya, Nishma; Parajuli, Ashish; Gorkhali, Amritee; Shrestha, Amir; Dangal, Ganesh (Journal of Chitwan Medical College, 2019)
Fetal liver tumors represent approximately 5% of all congenital tumors and hemangiomas account for approximately 15% of all fetal liver tumors. Hemangioma and hemangioendothelioma are benign vascular tumors but they are associated with a significant morbidity and mortality due to high output congestive heart failure and arteriovenous shunting. Ultrasound features of hepatic hemangioma can overlap with arteriovenous malformation. This is a case report of fetal hepatic hemangioma with aretriovenous shunting detected on routine anomaly scan at 20 weeks of gestation in 22 years old Nepalese women who was asymptomatic. Prenatally, a 3.2cm x 2.8cm multicystic mass was seen in the left hypochondrium of the fetal abdomen displacing the stomach. On color Doppler examination, the mass showed internal color flow and multiple tortuous dilated vessels noted around the lesion. After counseling regarding the lesion to the mother and her family; decision to abort the fetus was made. Autopsy was done for the final diagnosis of the lesion, which showed vascular mass in the left lobe of liver insinuating between stomach and spleen.